If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(1 + 3x) + -6x = 172 (1 * -8 + 3x * -8) + -6x = 172 (-8 + -24x) + -6x = 172 Combine like terms: -24x + -6x = -30x -8 + -30x = 172 Solving -8 + -30x = 172 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -30x = 172 + 8 Combine like terms: -8 + 8 = 0 0 + -30x = 172 + 8 -30x = 172 + 8 Combine like terms: 172 + 8 = 180 -30x = 180 Divide each side by '-30'. x = -6 Simplifying x = -6
| n-8=19-11 | | 9.21*9.21= | | n^2-12n+13=-7 | | 3(r-5)+2(r-4)=-2(r-1)+8(r+2) | | 8(7r+5)=320 | | 6x-5=109 | | 8(7r+5)=330 | | e^4x=e^2x+6 | | 2/3=2-2 | | 2a+14-13=-7 | | a^2+8a+6=-9 | | b-33=145 | | 4+2(2)+3x=11 | | 6(1-5v)=-234 | | 6-2n=-8+3(-4n-2) | | 1-3y/5-4=2y/3 | | 4(3x-5)-12(x-5)=70 | | 1+3x=4+4x | | (2x-7)y=15 | | x=x-u | | -10-9k=-91 | | -8x-3x-11=-8x+7 | | 3x-10(x+2)=sqrt(13)-7x | | -8x-3x-11=-8+7 | | 99=5n+9 | | 4(3x-5)+12(x-5)=70 | | 6-6(5+5m)=-24+8m | | X^2+5x+7=49 | | X^2+5x+58=0 | | R^3-r^2-4r+4=0 | | log(6x+8)=log(12) | | -7(8k-8)=-392 |